Target isolation of cytotoxic diterpenoid esters and orthoesters from Daphne tangutica maxim based on molecular networking. (November 2022) - Guo, Rui; Li, Qian; Mi, Si-Hui; Jia, Shu-He; Yao, Guo-Dong; Lin, Bin; Huang, Xiao-Xiao; Liu, Yu-Yang; Song, Shao-Jiang
Abstract: Guiding by LC-MS/MS analysis and the GNPS Molecular Networking, five undescribed daphnane diterpenoids, tanguticanines A–E, and eleven known analogues were discovered from the whole plants of Daphne tangutica Maxim. Their structures and absolute configurations were determined via extensive NMR spectroscopic analysis, ECD calculations, and X-ray diffraction crystallography. Tanguticanine E (5 ) exhibited promising cytotoxicity against the HepG2 cell line with an IC50 value of 9.93 ± 0.10 μ M. Further flow cytometry experiment was performed to detect cell apoptosis, and the results indicated that cytotoxic diterpenoids (tanguticanines B, D and E, altadaphnan C, gniditrin, hirsein A and simplexin) exert their effects through induction of apoptosis. Graphical abstract: Image 1 Highlights: New daphnane diterpenoids were isolated from D. tangutica by LC-MS/MS analysis. The structures were determined by NMR data, ECD calculations and X-ray diffraction. Tanguticanine E exhibited the most prominent cytotoxicity against HepG2 cells. Cytotoxic diterpenoids exert cytotoxic effects through induction of apoptosis.